Perl for C programmers - Oualline, Steve (Sams, 2002)
The Perl book written for the C and C++ programmer. Perl for C Programmers teaches what's similar and different between Perl and C/C++ and how to then utilize Perl to the fullest. 80% of the people who start using Perl for the first time come with a background in the C or C++ programming language. This book is written for those people. Perl is becoming one of the most common languages used in web development because of its powerful ability for text manipulation. There is a large need for Perl books that clearly explain how to use Perl in terms the reader can understand. The primary audience coming to learn Perl is C and C++ programmers.